2010
DOI: 10.1016/j.transproceed.2010.05.116
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Nonsurgical Complications of a Pig to Baboon Heterotopic Heart Transplantation Model

Abstract: A modified immunosuppressive regimen, developed at the National Institutes of Health, has been employed in a large animal model of heterotopic cardiac xenotransplantation. Graft survival has been prolonged, but despite this, our recipients have succumbed to various surgical or nonsurgical complications. Herein, we have described different complications and management strategies. The most common complication was hyperco-agulability (HC) after transplantation, causing thrombosis of both small and large vasculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…We have previously shown that by depleting B cells with anti-CD20 antibody, costimulation blockade by anti-CD154 antibody, and treatment with MMF, we can prolong cardiac xenograft survival in a pig-to-baboon model for up to 236 days [4]. Despite achieving significant graft prolongation in the above group of experiments, we encountered several complications leading to recipient death or need for euthanasia before the transplanted heart fully rejected [31]. In our experience and also by others, anti-CD154 antibody use resulted in complications including TM, CC, and bleeding [8,32].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that by depleting B cells with anti-CD20 antibody, costimulation blockade by anti-CD154 antibody, and treatment with MMF, we can prolong cardiac xenograft survival in a pig-to-baboon model for up to 236 days [4]. Despite achieving significant graft prolongation in the above group of experiments, we encountered several complications leading to recipient death or need for euthanasia before the transplanted heart fully rejected [31]. In our experience and also by others, anti-CD154 antibody use resulted in complications including TM, CC, and bleeding [8,32].…”
Section: Discussionmentioning
confidence: 99%
“…Some other complications experienced over the length of the project included abdominal bleeding. GI bleeding, aspiration pneumonia, seizures, thrombocytopenia and anemia (21). …”
Section: Discussionmentioning
confidence: 99%
“…This prompted us to study the risks of intracarotid cell transplantation and determine which factors are most relevant for developing safe injection protocols. Microvascular thrombosis is a major complication of solid organ xenografts 13,14 and, thus, we first hypothesized that the presence of xenogeneic cells in cerebral vessels may be a factor contributing to the thrombosis and subsequent strokes that we observed in our hGRP grafts. As human-to-rat is a discordant xenotransplantation, it activates the immune system more profoundly than concordant xenografts.…”
Section: Discussionmentioning
confidence: 99%